Development of ginger essential oils-nanobactericides for controlling bacterial leaf blight disease of rice caused by Xanthomonas oryzae pv. oryzae - Abdullahi, Adamu (2022)
The bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) have been found to be the major rice disease that causes significant loss of yield upon infection. The susceptible plants can result in the production losses of up to 50%. Scientists and farmers are increasingly paying more attention to the development of plant-based nanobactericides for disease management in order to lessen overdependence on chemical pesticides. A series of laboratory experiments were conducted in order to promote this development. These experiments concentrated on the extraction and characterization of the phytochemical compounds found in ginger essential oils (EOs), the suppression of the development of Xoo biofilm, and microscopic examinations. It was followed by nanobactericide evaluation of the antibacterial activity of Xoo. Three blocks were made for each treatment and three plants per replicate in a completely randomized block design. The essential oils (EOs) were extracted from fresh ginger rhizomes using a modified Clevenger-type apparatus by hydro-distillation, which were purchased from local producers in Bentong, Pahang. The chemical compositions of the EOs were then discovered and profiled using the analytical techniques of gas chromatography-mass spectroscopy (GCMS) and headspace procedures. Chemical compounds present in the EOs were monoterpenes such as trans-caryophyllene, camphene, geranial, eucalyptol, and neral, as well as sesquiterpene hydrocarbons mainly α-zingiberene, ar-curcumene, β-bisabolene, β-sesquiphellandrene which differ in their composition and concentrations. Food poisoned and disc diffusion techniques were applied on the tested pathogens to determine the percentage inhibition of fungal mycelial and bacterial growth inhibition, respectively. The EOs produced mycelial growth inhibition in all the test fungal pathogens which include (Fusarium oxysporum, Pyricularia oryzae, Colletotrichum falcatum, Ganoderma boninense, and Rigidoporus microporus Fusarium oxysporum, Pyricularia oryzae, Colletotrichum falcatum, Ganoderma boninense, and Rigidoporus microporus) after five days of incubation. The minimum inhibitory concentrations (MIC) and minimum fungicidal concentrations (MFC) of the EOs on the tested fungi were in the range of 1- 3 μL/mL and 5-6 μL/mL, respectively. The bacterial growth of all the tested isolates (Xanthomonas oryzae pv. oryzae- strain A, X. oryzae pv. oryzae- strain B, Ralstonia solanacearum, Bacillus sp. and Klebsiella sp.) was also affected by EOs at 100-500 μL/mL, from weak to strong antibacterial activity. The inhibition zone of positive control (streptomycin) at 15 μg/disc was 25.00 mm and appeared to be efficient. The MIC values of the EOs were in the range of 100 μL/mL to 200 μL/mL. The LC50 value resulting from exposure to the EOs varied among fungal and bacterial pathogens. Metabolomics analysis to concurrently quantify variability among multiple compounds in the data sets and identify such compounds responsible for the Xoo inhibition were determined. The cross validated PLS model has shown a strong correlation between ginger EOs and bioactivity. The action of ginger EOs on the cell structure of Xoo was fully identified using scanning electron microscope (SEM), transmission electron microscope (TEM) and confocal laser scanning microscope (CLSM) as well as biofilm formation. It was done by observing the changes in morphology and integrity of Xoo cells. The Dimethyl sulfoxide (DMSO) treatment (control) showed a normal rod shape cell, while treatment with the ginger EOs showed irregular shape with sunken surfaces, and treatment with antibiotics display abnormal growth of the cells. The ginger EOs display a wide range of activity against the pathogen. The biofilm of the Xoo strain has been formed. The EOs showed different optical density values measured due to the formation of Xoo biofilms and the inhibition percentage of Xoo biofilm. The results showed that the control (broth containing untreated Xoo cells) had the highest mean optical density value with a strong biofilm formation (2.459 O.D), followed by 31.25 μL/mL treatment. The inhibition percentage showed that the maximum inhibition was 76.33% at a concentration of 500 μL/mL. When the concentration of EOs was decreased, the Xoo biofilm inhibition declined. Problems of volatility, solubility, and stability of EOs lead to the use nanotechnology via nanoemulsions approach. The preparation of nano-emulsion of ginger EOs have prepared. A ternary phase diagram (TPD) was developed using a low-energy method based on nonionic surfactant Tween 20, water, and EOs as the active ingredient. Four formulations of nanobactericides coded as A1, A2, A3 and A4 were chosen from the single-phase ternary phase diagram for preliminary screening after constructing TPD. They were tested for their stability and thermostability over time at 54°C and 28°C. Finally, A4- is the best formulation that displays a single, low viscous and watery phase that is stable following physiochemical property measures. Usage of the developed nanobactericides have been applied both in- vitro and in-vivo to evaluate its efficiency to the pathogens. The in-vitro antibacterial activity of the nanobactericides was measured by the presence or absence of inhibition zones. The growth of the tested pathogens was affected by the different concentration of the formulation ranging from 50-125 μL/mL. The findings showed significant antibacterial activity against Xoo, Bulkholderia glumae Ralstonia solanacearum, and least effective against Erwinia chrysanthemi at higher concentrations. Glasshouse application showed that the disease symptoms decrease more gradually to nanobactericides due to its phytoconstituents. Three concentrations of formulation were tested containing 75, 100, and 125 μL/mL. Findings of research revealed that treatment 125 μL/mL was the best treatment based on suppression of disease severity index, area under the disease progress curve (AUDPC) value as well as plant height, physiological and yield parameters when compared to the positive control. In conclusion, developed nanobactericides could be used as a new antimicrobial agent in suppressing the growth of Xoo in-vitro and suppress disease severity index of bacterial leaf blight disease in-vivo trials and as a promising new alternative to synthetic bactericides.